Penerapan Asas Keterbukaan Informasi Publik pada Institusi Tentara Nasional Indonesia dikaitkan dengan Data Kerahasiaan Negara - Saputro, Dwi Suryo; Satriya, Bambang (Postgraduate University of Merdeka Malang, 2023)
This article examines and analyzes the application of the principle of openness in the Indonesian National Army institution while maintaining state secrets and the obstacles experienced as well as the efforts of the TNI institution in implementing the principle of openness to public information while maintaining state secrecy. The method used is an empirical legal research method and uses a sociological approach. The results show that state secrets should be part of national security which has an important role in safeguarding strategic/tactical information owned by a country/government. The existence of state secrets must also not compromise the interests of citizens. State secrecy practices directly and indirectly are of course related to individual rights and freedoms which must also be protected. This provision is regulated in Article 17 letter c of the KIP Law which stipulates that every Public Body is obliged to provide access for every Public Information Applicant to obtain public information, except for public information which, if opened and given to the Public Information Applicant, could endanger the defense and security of the State. The application of the principle of openness in the Indonesian National Army Institutions while maintaining state secrets is carried out by classifying information, objects and activities of the Indonesian National Army according to the provisions of Article 17 of the Law on Openness of Public Information. If the leak of information, objects and activities from the Indonesian National Army can cause various problems including the loss of state sovereignty and the disintegration of the nation, then this information, objects and activities are state secrets which must not be shared with the public. Furthermore, the obstacle in implementing the principle of openness while maintaining state secrets is in terms of human resources, where TNI members do not really understand the rules regarding matters that can be categorized as state secrets and those that are not. Apart from that, suboptimal supervision could also be the cause of the principle of information disclosure not being implemented properly in TNI institutions.